Influence of Fly Ash Variation on the Compressive Strength of Solid Lightweight Bricks for Non-Structural Wall - Selvialesti, Jessy; Supriyadi, Asep; Sutandar, Erwin (Jurnal Teknik Sipil, 2025)
Kalimantan Barat is characterized by peat and soft soils with low bearing capacity. Excessive loads on these soil types can cause significant soil subsidence, increasing the cracks risk in building structures. Alongside advancements in science and technology in the construction sector, sustainable building material innovations continue to be developed, one of which is using lightweight bricks as an alternative wall material. This study aims to evaluate the manufacturing method of lightweight bricks based on rice husk fibre and to analyze the effect of varying fly ash content on their physical and mechanical properties, referring to the SNI 8640:2018 standard. The fly ash compositions used were 0%, 35%, 40%, 45%, and 50%. Tests included visual inspection, bulk density, water absorption, sound and heat resistance, drying shrinkage, fire resistance, compressive strength, and tensile strength. The results show that adding fly ash significantly influences the brick"™s performance. The variation with 35% fly ash addition (Variation 2) demonstrated the most optimal performance, achieving the best balance between mechanical strength, thermal resistance, and physical characteristics by the SNI 8640:2018 standard. This study confirms that rice husk fibre lightweight bricks have the potential as an environmentally friendly alternative building material that meets technical standards.